N-Propionyl polysialic acid precursor enhances the susceptibility of multiple myeloma to antitumor effect of anti-NprPSA monoclonal antibody - Xiong Hong; Liang Ai-bin; Xiu Bing; Fu Jian-fei; Ding Yi; Chen Yu-hua (Acta Pharmacologica Sinica, 2016)
Aim: To study the antitumor effect of anti-NprPSA monoclonal antibody (mAb) in combination with ManNPr, a precursor of N-propionyl PSA, in multiple myeloma (MM), and to explore the mechanisms of the action. Methods: Human multiple myeloma cell line RPMI-8226 was tested. The cells were pre-treated with ManNPr (1, 2, and 4 mg/mL), and then incubated with anti-NprPSA mAb (1 mg/mL). Cell apoptosis in vitro was detected using MTT assay and flow cytometry. BALB/c nude mice were inoculated sc with RPC5.4 cells. On 5 d after the injection, the mice were administered sc with anti-NprPSA mAb (200 μg/d) and ManNPr (5 mg/d) for 8 d. The tumor size and body weight were monitored twice per week. TUNEL assay was used for detecting apoptosis in vivo. The apoptotic pathway involved was examined using Western blot analysis and caspase inhibitor. Results: Treatment of RPMI-8226 cells with anti-NprPSA mAb alone failed to inhibit cell growth in vitro. In RPMI-8226 cells pretreated with ManNPr, however, the mAb significantly inhibited the cell proliferation, decreased the viability, and induced apoptosis, which was associated with cleavage of caspase-3, caspase-8, caspase-9, and poly(ADP-ribose) polymerase. In the mouse xenograft model, treatment with the mAb in combination with ManNPr significantly inhibited the tumor growth, and induced significant apoptosis as compared to treatment with the mAb alone. Moreover, apoptosis induced by the mAb in vivo resulted from the activation of the caspases and poly(ADP-ribose) polymerase. Conclusion: The anti-NprPSA mAb in combination with ManNPr is an effective treatment for in vitro and in vivo induction of apoptosis in multiple myeloma.